2019
DOI: 10.1002/adfm.201905340
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsically Stretchable High‐Performance Polymer Semiconductor with Low Crystallinity

Abstract: For wearable and implantable electronics applications, developing intrinsically stretchable polymer semiconductor is advantageous, especially in the manufacturing of large-area and high-density devices. A major challenge is to simultaneously achieve good electrical and mechanical properties for these semiconductor devices. While crystalline domains are generally needed to achieve high charge carrier mobilities, amorphous domains are necessary to impart stretchability. Recent progresses in the design of high-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
227
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 141 publications
(234 citation statements)
references
References 72 publications
6
227
1
Order By: Relevance
“…[ 1–5 ] Continuous monitoring of typical physiological data such as respiration rate, heart rate, contraction/expansion of muscles, and ground reaction forces through the sensors is particularly important for the understanding of human physiology and phenotypes that lead from health to diseases ( Scheme a). [ 6–10 ] One of the fundamental units of wearable electronics is a stretchable display that simultaneously visualizes signals from the “bodyNet” and provides feedback to the system. [ 11–16 ] However, existing organic and quantum‐dot (QD) light‐emitting devices are degraded by various molecular interactions with oxygen and water.…”
Section: Methodsmentioning
confidence: 99%
“…[ 1–5 ] Continuous monitoring of typical physiological data such as respiration rate, heart rate, contraction/expansion of muscles, and ground reaction forces through the sensors is particularly important for the understanding of human physiology and phenotypes that lead from health to diseases ( Scheme a). [ 6–10 ] One of the fundamental units of wearable electronics is a stretchable display that simultaneously visualizes signals from the “bodyNet” and provides feedback to the system. [ 11–16 ] However, existing organic and quantum‐dot (QD) light‐emitting devices are degraded by various molecular interactions with oxygen and water.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, polymers based on the extended fused-ring IDT core display high FET mobilities with high backbone coplanarity despite the lack of long-range crystalline order in the solid state. 2,3,[25][26][27][28] This intriguing feature considerably differs from the abovementioned theory and provides a new molecular-design guideline for achieving high mobilities in near-amorphous polymers, thus facilitating the development of intrinsically stretchable semiconducting polymers toward next-generation electronics. Driven by their unique, yet different properties, many polymers based on CDT and IDT units have been incorporated into high-performance FETs and continue to be studied (see Fig.…”
Section: Introductionmentioning
confidence: 93%
“…π-conjugated polymers have been extensively studied for their application in printing organic eld-effect transistor (FET) arrays and circuits to realize low-cost, large-area, exible, and even stretchable nextgeneration electronics that cannot be realized using traditional silicon technologies. [1][2][3][4][5][6][7] On the basis of the principle that charge carrier mobility is unambiguously linked to the degree of order in the packing, more than a decade of research has focused on increasing the crystallinity of π-conjugated polymers as a strategy for improving charge transport; this has reliably boosted mobility to exceed 10 cm 2 V − 1 s − 1 . 8−13 Three major design strategies exist for enforcing polymer crystallinity: (i) donor-acceptor architecture in the backbone induces a strong intramolecular charge transfer (ICT) effect as an attractive force between the donor and acceptor units, resulting in a more planar con guration that facilitates πelectron delocalization along the backbone; [14][15][16][17] (ii) the incorporation of fused aromatic building segments into the backbone generates a large π-orbital overlapping area, formulating large crystalline domains with only few disordered domain boundaries; 12, 18−21 and (iii) a precise regioregularity in the polymer repeating units realizes enhanced structural arrangement of the chains, thus promoting selforganization.…”
Section: Introductionmentioning
confidence: 99%
“…[911] Many recent studies have focused on the innovation of intrinsically stretchable materials, such as semiconductors and dielectrics, for high-performance-printed stretchable thin-film transistors. [400,444,609,[912][913][914] For instance, Wang et al reported an intrinsically stretchable transistor array for signal manipulation and computation. [271] The SEBS, 'conjugated polymer/elastomer phase separation induced elasticity' (CONPHINE) film, and CNTs were used as the dielectric, semiconductor, and electrodes, respectively.…”
Section: Transistorsmentioning
confidence: 99%